If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-a+3a=-6
We simplify the equation to the form, which is simple to understand
-a+3a=-6
We move all terms containing a to the left and all other terms to the right.
-1a+3a=-6
We simplify left and right side of the equation.
+2a=-6
We divide both sides of the equation by 2 to get a.
a=-3
| 8=7y+3 | | (8x+7h)(8x+7h)= | | -2a-3a=-5 | | 6k+5k=-11 | | 6-4x=78 | | -68=-3+5(3x-4) | | 66=4t-15t | | 2(6v-3)=-66 | | 2=x+4+x | | -2x-4+3=9 | | m-5m=-8 | | 84=7(v-79) | | -9+p/2=-12 | | 6+4x=6x-9 | | -7x+9=4x+141 | | 30y+20-3=7 | | 3x-1=-4x+6 | | 8y-4-5=5 | | 2/3(1/2) | | -2+x+7x=-50 | | -w-(3x-3w)+x= | | 3x+1+3x=-53 | | -3=1/3k | | -2u+6=-10 | | t/2-1=2 | | h-90/4=-2 | | -2=h-90/4 | | k-81/8=2 | | -13+8c=27 | | 2v+18=46 | | 2(v-40)=88 | | q/3-(-4)=7 |